179 WHAT IS THE RISK OF FALLS DUE TO PSYCHOTROPIC MEDICATIONS IN A LARGE POPULATION-REPRESENTATIVE COHORT OF COMMUNITY-DWELLING OLDER PEOPLE?. (25th October 2022) - Gallagher, E; Mehmood, M; Lavan, A; Kenny, RA; Briggs, R
Abstract: Background: Psychotropic medications including antidepressants, anticholinergics, benzodiazepines, 'Z' drugs and antipsychotics, are frequently identified as Falls Risk Increasing Drugs (FRIDS), yet there is a relative lack of robust data detailing the prospective risk of falls associated with these drug classes. Methods: Participants aged ≥65 years from the Irish Longitudinal Study on Ageing (TILDA) were included and followed from Waves 1 to 5 (Mean 7.6 years follow-up). Incidence of falls was ascertained by self-report and unexplained falls were defined as falls not caused by a slip or trip with no apparent cause. Medication lists were examined for medications of interest. Logistic Regression models, reporting odds ratio with 95% confidence intervals, were used to assess the association between medication classes and incident fall types and were adjusted for relevant covariates. Results: 2, 090 participants were included (mean age at baseline 72 years, 53% female). During follow-up, over half of participants (52%, n=1, 089) had a fall, with one quarter (25%, n=526) reporting an unexplained fall and almost one fifth (19%, n=394) reporting a fall causing injury. Anti-depressants were associated with an increased risk of falling (OR=3.01, 1.98-4.58, p<0.001), injurious falls (OR=1.96, 1.37-2.81, p<0.001) and unexplained falls (OR=2.71, 1.88-3.91, p<0.001) in fully adjusted models. Anti-cholinergic medications were associated with an increased risk of falling (OR=1.79, 1.11-2.88, p=0.017) and of unexplained falls (OR=1.89, 1.19-3.01, p=0.007). 'Z' drugs were associated with an increased risk of falling (OR=2.96, 1.64-5.32, p<0.001) and of injurious falls (OR=2.05, 1.26-3.34, p=0.004). Benzodiazepines and Anti-psychotics were not associated with incident falls in fully adjusted models. Conclusion: Anti-depressants, anti-cholinergic medications and 'Z' drugs are independently associated with an increased falls risk. Given the profound impact falls can have on functional trajectory and quality of life, regular review of ongoing need for these medications should be central to the comprehensive geriatric assessment.